197k views
5 votes
Examine the equation.

–2(–x + 9) = 2(x – 9) 2x – 18 = 2x – 18

This equation has:
A. one solution
B. infinitely many solutions
C. no solution

2 Answers

6 votes

The answer is B.

Hope this helps :)

User Bart Burg
by
5.8k points
2 votes

Answer:

B. infinitely many solutions

Explanation:

–2(–x + 9) = 2(x – 9)

Distribute the -2 on the left side. Distribute the 2 on the right side.

2x - 18 = 2x - 18

Add 18 to both sides.

2x = 2x

The equation means two times a number x is equal to two times the same number x. This is true for all numbers x. Every number is a solution of this equation.

Answer: B. infinitely many solutions

User Stephan
by
6.5k points